Re-centering the teacher agency narrative: educators reflecting on context, positionalities, and situated identities - Kavimandan, Shabina (Kansas State University, 2021)
The purpose of this qualitative study was to examine the extent of teacher agency in response to a culturally responsive professional development model. This study aimed at findings results from a three-year professional development intervention provided to educators in a highly diverse school district. Teachers participated in a combination of whole group professional development sessions and smaller staff in-services that were provided on a bi-weekly basis. Biography Driven Instruction (BDI), the professional development intervention that was at the heart of this phenomenological case study provided an impetus to concentrate on teachers’ action-oriented responses as exhibited through (a) their positionality within the context of the school, (b) the context they work in and roles they play within these contexts, (c) the extent of their instructional, pedagogical, and curricular agency and the decisions they make within their instructional settings, and (d) their own professional identity negotiations in response to the BDI PD. Further, this study examined the extent of teachers' professional agency in response to context-specific, culturally responsive professional development within a highly diverse school district. Doing so it has also aimed to shed light on teachers' professional identity negotiations and educational change, as well as contribute to the discussions on how school districts adopt and develop educational programs. To further these much-needed conversations on agency, for this study the influence of teachers and their capacity for the agency was examined in relation to the following interrelated components: (a) teachers’ action-oriented response to professional development, (b) factors that might cause dissonance between teachers’ own beliefs and the change they are being asked to make (Buchanan, 2015), and (c) any impact of contextual factors such as teacher’s own positionality and the context within which they work. Following five major themes were developed from the gathering and reviewing of data: • sense of empowerment for self and students • situatedness of identity • intentionality and control of actions • sense of agency in instruction and planning • curriculum: a nomenclature or a means to an end The findings gave insights into the psychological attachment that these participants have found to their profession and how BDI in part has been responsible for this attachment. The participants overwhelmingly talked about the source of their agency being the outcomes their students exhibited. The importance of fostering relationships with students was highlighted repeatedly by the participants. There are several implications for pre-service and novice educators as well. Of utmost importance is the need to provide professional development that provides novice teachers with opportunities to understand the biographies of their students and connect with their classroom communities in order to fully realize the extent of their agencies. The following research question was at the heart of this study on agency: How does a professional development model grounded within a culturally responsive framework help teachers perceive the extent of their agency?
Keywords: Teacher agency; Culturally responsive teaching; Professional development; Positionality; Teaching context